EEPD1 regulates inflammation and endothelial apoptosis in atherosclerosis through KLF4‐EEPD1‐ERK axis - Kaiwen Yu; Xiang Li; Xin Shi; Ruogu Li; Min Zhang (Clinical and Translational Medicine)
Abstract Background Inflammation and endothelial apoptosis are implicated in the advancement of atherosclerosis. EEPD1 holds a pivotal position in the repair of DNA damage and contributes to the progression of multiple cancers. However, the role of EEPD1 in cardiovascular diseases needs to be explored further, especially in atherosclerosis. Methods We constructed EEPD1 and ApoE (apolipoprotein E)‐deficient mice to assess how EEPD1 influences endothelial inflammation and apoptosis within atherosclerotic plaques. High‐throughput RNA sequencing of human aortic endothelial cell groups treated with siCon+TNFα and siEEPD1+TNFα identified notable disparities in the MAPK pathway between groups. Chromatin immunoprecipitation and luciferase reporter assay confirmed that KLF4 directly regulates EEPD1. Results Further examination of gene expression data revealed elevated EEPD1 concentrations in atherosclerotic plaques of patients, which findings were corroborated in the aortas of ApoE−/− mice. Present study demonstrated that adhesion molecule expression, endothelial apoptosis, aortic root plaques and macrophage accumulation were markedly ameliorated in EEPD1−/−ApoE−/− mice compared to WT ApoE−/− mice. Functional analysis revealed that increase in EEPD1 promotes ERK phosphorylation and significantly increases endothelial apoptosis and inflammation in atherosclerosis, which was abrogated by inhibition of ERK phosphorylation. We found KLF4 to be the transcription repressor of EEPD1 through luciferase assay and chromatin immunoprecipitation, and KLF4 inhibition abrogated the amelioration of endothelial apoptosis and inflammation caused by EEPD1 deletion. Conclusions Collectively, this study revealed that EEPD1 deletion can lead to amelioration of atherosclerosis through the KLF4‐EEPD1‐ERK axis. Hence, targeting EEPD1 could be a promising therapeutic strategy for patients with atherosclerosis.